The Role Of Audit Committee In Moderating Tax Avoidance In Indonesia - Moeljono; Masine Slahanti; Rahoyo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study tries to analyze the relationship between Size, ROA and DER on Tax Avoidance with the mediating variable of the Audit Committee.The nature of quantitative research uses Eviews 12 analysis tools to build relationships between variables. The sample uses purposive sampling technique, with the sample criteria being companies listed on the Indonesia Stock Exchange, while the population is taken according to what has been previously determined. To conduct the analysis, 27 sample companies were obtained and analyzed using the best method so that the maximum test results were obtained.The results of the research show that Size, DER, and ROA have no effect on Tax Avoidance nor do they mediate the Audit Committee variable. The weakness of this relationship proves that there are many factors that affect the process of tax avoidance practices. Furthermore, tax avoidance practices by companies may not be influenced by the company's internal environment, so the biggest factor may be from outside the company.The practice of tax avoidance by companies in Indonesia which has been indicated to come from internal companies is not entirely true. factors such as Size, ROA, DER have no effect on tax avoidance. The Audit Committee as a Moderating Variable also failed to moderate Size, ROA, DER on Tax Avoidance Practices. This is possible from outside the company as a factor influencing corporate tax avoidance in Indonesia.